Teens with Type 1 Diabetes: How Does Their Nutrition Measure Up? - Eleanor Race Mackey; Lyndsay O’Brecht; Clarissa S. Holmes; Marni Jacobs; Randi Streisand (Journal of Diabetes Research)
Objective. To characterize the intake of macronutrient and fiber in adolescents with type 1 diabetes (T1D) and examine their association with health indicators. Methods. Baseline data from an RCT were examined. Adolescent-parent dyads (n=257, mean age 12 ± 1.2 years, 49.4% girls) reported dietary intake via two separate 24-hour recall interviews during a two-week period. Demographic and medical variables were abstracted from questionnaires and medical charts. Results. Controlling for demographic and diet variables, a higher percentage of daily energy intake from fats was associated with poorer HbA1c. In contrast, an association between higher percent of energy intake from proteins and carbohydrates was found with higher systolic and diastolic BP, respectively. Conclusions. Many early adolescents with T1D did not meet diabetes nutritional guidelines. Lower adherence to nutritional guidelines, specifically more than recommended energy intake from fats, was associated with poorer HbA1c. Addressing nutritional guidelines and increasing adherence as part of treatment may improve health outcomes for youth with T1D.